2010
DOI: 10.1063/1.3373389
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theoretical study of pentacene/noble metal interfaces with van der Waals corrections: Vacuum level shifts and electronic structures

Abstract: In order to clarify factors determining the interface dipole, we have studied the electronic structures of pentacene adsorbed on Cu͑111͒, Ag͑111͒, and Au͑111͒ by using first-principles density functional theoretical calculations. In the structural optimization, a semiempirical van der Waals ͑vdW͒ approach ͓S. Grimme, J. Comput. Chem. 27, 1787 ͑2006͔͒ is employed to include long-range vdW interactions and is shown to reproduce pentacene-metal distances quite accurately. The pentacene-metal distances for Cu, Ag,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
161
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(189 citation statements)
references
References 76 publications
22
161
3
2
Order By: Relevance
“…The experimental evidence 19,48,49 indicates that this interface dipole is 0.95 eV, in good agreement with our results. Morikawa et al 20 have calculated an interface dipole of 1.19 eV for a 6 × √ 7 pentacene/Au(111) structure and a pentacene-Au distance of 3.2 Å; the interface dipole and the metal/organic distance are both in good agreement with our calculations.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The experimental evidence 19,48,49 indicates that this interface dipole is 0.95 eV, in good agreement with our results. Morikawa et al 20 have calculated an interface dipole of 1.19 eV for a 6 × √ 7 pentacene/Au(111) structure and a pentacene-Au distance of 3.2 Å; the interface dipole and the metal/organic distance are both in good agreement with our calculations.…”
Section: Discussionsupporting
confidence: 78%
“…In a second step, we calculate the WCI (thin red curve) and add the C 6 /r 6 -like van der Waals energy (thin green curve) to obtain the total energy (thick green curve). Therefore, we obtain an equilibrium distance of around 3.2 Å, similar to the one found in other calculations, 20 and a binding energy of 1.8 eV per molecule. This energy overestimates by ∼ 0.7 eV the experimental value of ∼ 1.1eV, 38 probably due to the approximation used for the factor f D (R).…”
Section: A Methods Of Calculationsupporting
confidence: 68%
See 2 more Smart Citations
“…6, in agreement with experimental observations 10,45,46 . Our results are also in good agreement with previous theoretical studies: from PBE calculations we found d = 3.938Å and E ads = −0.119 eV, which compare well with previous GGA results (d = 3.7-4.12Å and E ads within the range of −0.078 to −0.108 eV) 47,48 ; using the PBE+vdW surf method we found d = 2.910Å and E ads = −2.396 eV, which is in good agreement with previous results obtained by Toyoda et al 47 using the pairwise DFT-D method (d = 2.9Å and E ads = −2.28 eV), but differ from the values obtained by the same authors using the nonlocal vdW-DF method (d = 3.7Å and E ads = −1.62 eV) 47 . It should be pointed out that the vdW-DF method tends to overestimate the adsorption heights, even though it provides reliable adsorption energies 12,22 -recent vdW-DF functionals (e.g., optB86b-vdW and rev-vdW-DF2), however, have been shown to give both accurate adsorption height and energy 49 .…”
Section: B Pentacene On Ag(111)supporting
confidence: 82%